Fabrication and characterization of non-resonant magneto-mechanical low-frequency vibration energy harvester. (1st March 2018) - Nammari, Abdullah; Caskey, Logan; Negrete, Johnny; Bardaweel, Hamzeh
Highlights: A novel magneto-mechanical nonlinear vibration energy harvester is presented. The harvester is hand-held with approximately 100.5 cm 3 volume. The harvester generates 3.5 V and 0.133 mW/cm 3 g 2 at 15.5 Hz and 1.0 g [m/s 2 ]. The harvester is broadband and suitable for low frequency energy harvesting. Abstract: This article presents a non-resonant magneto-mechanical vibration energy harvester. When externally excited, the energy harvester converts vibrations into electric charge using a guided levitated magnet oscillating inside a multi-turn coil that is fixed around the exterior of the energy harvester. The levitated magnet is guided using four oblique mechanical springs. A prototype of the energy harvester is fabricated using additive manufacturing. Both experiment and model are used to characterize the static and dynamic behavior of the energy harvester. Measured restoring forces show that the fabricated energy harvester retains a mono-stable potential energy well with desired stiffness nonlinearities. Results show that magnetic spring results in hardening effect which increases the resonant frequency of the energy harvester. Additionally, oblique mechanical springs introduce geometric, negative, nonlinear stiffness which improves the harvester's response towards lower frequency spectrum. The unique design can produce a tunable energy harvester with multi-well potential energy characteristics. A finite element model is developed to estimate the average radial flux density experienced by the multi-turn coil. Also, a lumped parameter model of the energy harvester is developed and validated against measured data. Both upward and downward frequency sweeps are performed to determine the frequency response of the harvester. Results show that at higher excitation levels hardening effects become more apparent, and the system dynamic response turns into non-resonant. Frequency response curves exhibit frequency jump phenomena as a result of coexistence of multiple energy states at the frequency branch. The fabricated energy harvester is hand-held and measures approximately 100.5 [cm 3 ] total volume. For a base excitation of 1.0 g [m/s 2 ], the prototype generates a peak voltage and normalized power density of approximately 3.5 [V] and 0.133 [mW/cm 3 g 2 ], respectively, at 15.5 [Hz].